Do biopores created by perennial fodder crops improve the growth of subsequent annual crops? A synthesis of multiple field experiments - Dominik Behrend; Miriam Athmann; Eusun Han; Paul Martin Küpper; Ute Perkons; Sara L. Bauke; Ulrich Köpke; Timo Kautz; Thomas Gaiser; Sabine J. Seidel (Field Crops Research, 2025)

Plant and soil N of different winter cover crops as green manure for subsequent organic white cabbage - Sophie Stein; Jens Hartung; Ute Perkons; Kurt Möller; Sabine Zikeli (Nutrient Cycling in Agroecosystems, 2023)
Leguminous cover crops used as green manures can reduce fertilizer inputs by supplying nitrogen (N) via mineralization of incorporated N-rich biomass derived from biological N 2 fixation. In a multi-year trial at three locations in Germany, the effects of leguminous, non-leguminous and mixed green manure crops on the yield of the subsequent cash crop white cabbage ( Brassica oleracea convar. capitata var. alba ) were investigated. The winter cover crop treatments were forage rye ( Secale cereale L.), a mixture of forage rye with winter Hungarian vetch ( Vicia pannonica Crantz), sole-cropped winter Hungarian vetch, winter pea ( Pisum sativum L.), and winter faba bean ( Vicia faba L.) with bare soil as a control. Sole-cropped legumes showed higher marketable cabbage head yields (head weight > 1.0 kg) compared to the other cover crop treatments, with 25.5, 25.9 and 28.1 Mg ha − 1 for vetch, pea and faba bean, respectively. The aboveground biomass of the legume winter cover crop treatments had higher N offtakes with 185, 177 and 159 kg N ha − 1 for vetch, pea and faba bean, respectively, with significantly lower carbon (C)/N ratios compared to rye and rye with vetch. The constant C/N ratio of the aboveground biomass of leguminous cover crops throughout the growing period indicates that the optimum incorporation date to achieve high N mineralization rates is less time dependent in leguminous compared to non-leguminous cover crops. The results of the present study show that leguminous winter cover crops do not reduce the soil N availability for a succeeding high N demanding cabbage crop resulting in yields comparable to agricultural practice without winter cover crops.

Can precrops uplift subsoil nutrients to topsoil? - Eusun Han; Feng Li; Ute Perkons; Paul Martin Küpper; Sara L. Bauke; Miriam Athmann; Kristian Thorup-Kristensen; Timo Kautz; Ulrich Köpke (Plant and Soil, 2021)

Root growth dynamics inside and outside of soil biopores as affected by crop sequence determined with the profile wall method - Eusun Han; Timo Kautz; Ute Perkons; Daniel Uteau; Stephan Peth; Ning Huang; Rainer Horn; Ulrich Köpke (Biology and Fertility of Soils, 2015)

Quantification of soil biopore density after perennial fodder cropping - Eusun Han; Timo Kautz; Ute Perkons; Marcel Lüsebrink; Ralf Pude; Ulrich Köpke (Plant and Soil, 2015)

Barley roots are not constrained to large-sized biopores in the subsoil of a deep Haplic Luvisol - Timo Kautz; Ute Perkons; Miriam Athmann; Ralf Pude; Ulrich Köpke (Biology and Fertility of Soils, 2013)